Metabolic effects of CoCr-enriched medium on shear-stressed endothelial cell and osteoblasts: A possible mechanism involving a hypoxic condition on bone healing - da Costa Fernandes, Célio Junior [UNESP] (2021)
Cobalt-chromium (CoCr)-based alloys have emerged as an interesting biomaterial within biomedical field, mainly considering their biocompatibility, resistance to corrosion and absence of magnetism; however, its effect on cell metabolism is barely known and this prompted us better evaluating whether CoCr-enriched medium affects the metabolism of both osteoblast and endothelial cells, and also if there is a coupling between them. This is also considered here the already-known effect of Cobalt (Co) as a hypoxic element. Firstly, discs of CoCr [subjecting (W) or not (Wo) to dual acid-etched (DAE)] were incubated into FBS-free cell culture medium up to 24 h (37 °C). This CoCr-enriched medium was further used to treat shear-stressed endothelial cells cultures up to 72 h. Thereafter, the conditioned medium containing metabolites of shear-stressed endothelial cells in response to CoCr-enriched medium was further used to subject osteoblast's cultures, when the samples were properly harvested to allow the analysis of the molecular issues. Our data shows that CoCr-enriched medium contains 1.5 ng–2.0 ng/mL of Co, which was captured by endothelial cells and osteoblasts in about 30% in amount and it seems modulate their metabolic pathways: shear-stressed endothelial cells expressed higher profile of HIF1α, VEGF and nNOS genes, while their global profile of protein carbonylation was lower than the control cultures, suggesting lower oxidative stress commitment. Additionally, osteoblasts responding to metabolites of CoCr-challenged endothelial cells show dynamic expression of marker genes in osteogenic differentiation, with alkaline phosphatase (ALP), osteocalcin, and bone sialoprotein (BSP) genes being significantly increased. Additionally, tensional shear-stress forces decrease the stimulus for ColA1gene expression in osteoblasts responding to endothelial cells metabolites, as well as modifying the extracellular matrix remodeling related genes. Analyzing the activities of matrix metalloproteinases (MMPs), the data shows that shear-stressed endothelial cells metabolites increase the activities of both MMP9 and MMP2 in osteoblasts. Altogether, our data shows for the first time that shear-stressed endothelial metabolites responding to CoCr discs contribute to osteogenic phenotype in vitro, and this predicts an active crosstalk between angiogenesis and osteogenesis during osseointegration of CoCr alloy and bone healing, maybe guided by the Co-induced hypoxic condition.